PENGARUH PELATIHAN PELAYANAN PRIMA TERHADAP KEPUASAN PELANGGAN RAWAT JALAN DI RUMAH SAKIT PERMATA HATI DURI - Nofiyadi Nofiyadi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
Satis factioni sastate that is felt by a person(client/patient) after suffering an actor result of the action that meets his expectations. Excellent service area ctivitie sunder taken by business ownersin the sale orserving customers make the best. At the hospital jewel heart thorn number of out patient visit sin 2013were76001 patients, but from the initial survey conducted in one hundred visitors valuation given by the patient after receiving out patient services at Permata Hati Hospital spines of 100 consumers 37 patients gave values 6, 30 patients gave a scoreof 5, and only 5 patients who provide value above 7, and there are patients who give value under five by 2 patients. This study was conducted to determine the effec to ftraining on the excellent service of the officer sout patient patient satis faction seen from there lationship between worker sand patients (friendliness, Informative, Communicative, Responsive, Supportive and Deftofficersin providing services). This study is ananalytic comparative pair swith out control, by using the one-group pretest-posttest design. With the number of samplesas the recipien to fallemployees of the hospital intervention Permata Hati Duri located in out patient installation, while the appraiserisan out patient 100 patients. From the data processing using the Wilcoxontest showed there is a causal relationship between the training of excellent service to the satisfaction of the patients seen in the hospitality P Value 0.001, P Value 0.001 Informative, Communicative P Value 0.001, P Value 0.001 Responsive, Supportive Deft P Value 0.001 and P Value 0,021. From there search it can besaid there is a causal relationship between the training excellent service with patient satisfaction, the hospital management recommended more frequent training of excellent service based on complaints receivedei ther from the patientor from the officers them selves.